The First Observational Study of Acute Medical Unit in Qatar - Abdel-Naser Elzouki; Phool Iqbal; Mohammed Zahid; Ijaz Kamal; Anand Kartha; Mustafa Al-Tekreti; Dabia Al-Muhanadi; Ahmed Al-Mohamed (Avicenna Journal of Medicine)
Background Acute medical unit (AMU) is a dedicated facility to treat patients with acute medical conditions requiring a short hospital stay (< 72 hours) with the support of a multidisciplinary team led by a medical consultant. We aim to present a study of the AMU model of care from Qatar to provide insight into its effects on patient care and management.